Comparison of athletic trainer stress and job satisfaction with different models of care delivery - Baker, C. S.; Wilkerson, G. B. (International Journal of Athletic Therapy & Training, 2018)
A patient-centered model (PCM) for athletic training services may function as a better model to decrease athletic trainer (AT) stress and result in a more desirable work-life balance compared to the traditional model (TM). The purpose of this study was to assess differences in AT stress and job satisfaction between healthcare models for delivery of AT services. A one-time electronic stress survey was administered to ATs working in both settings. ATs who work in the TM are more likely to report greater work-related stress, and less likely to report job satisfaction than ATs who work in the PCM setting.